Sea surface wind speed and sea state retrievals from dual-frequency altimeter and its preliminary application in global view of wind-sea and swell distributions. Issue 10 (19th May 2018) - Li, Shuiqing; Shen, Hui; Hou, Yijun; He, Yijun; Bi, Fan
ABSTRACT: Altimeter radar backscatter intensity, in terms of the normalized radar cross section (NRCS), is known to be modulated by surface wind forcing and the state of wind-sea development. Based on a data set of collocated altimeters (including Topex/Poseidon, Jason-1 and Jason-2) and in situ measurements, different responses to various wind speeds and wave ages (i.e. the state of wind-sea development) were illustrated for altimeter dual-frequency NRCSs (Ku -band at 13.6 Hz and C band at 5.4 Hz), which can facilitate the retrieval of wind speed and wave age parameters. A statistical parametric algorithm was developed to retrieve the two dynamic parameters from the altimeter dual-frequency NRCSs using the neutral network method. The wind-sea significant wave height (SWH) was estimated from wind speed and wave age parameters, which partitions the swell SWH from the altimeter SWH measurement. All newly derived parameters were well validated by comparison against in situ buoy measurements. A preliminary application of the method in examining the swell or wind-sea contributions to global waves was performed; it was found the swell dominance in an open ocean, and the wind-sea dominance in marginal and semi-enclosed seas. The methods would benefit other applications such as studies of air–sea interactions, validation of wave model, determination of swell decay rate and studies of wave climate.